Hybrid Force/Position Control of UR10 Robot Manipulator for Electrode Pasting Operation - Mohd Zani, Muhammad Zaihan Amni; Wan Zakaria, Wan Nurshazwani (Evolution in Electrical and Electronic Engineering, 2022)
The pasting operation is to assemble tubes (either 2 poles or 3 poles) which are mounted into sealing graphite for electrode ceramic tubes. This is one of the operations that is conducted in TDK Electronics for electrode ceramic tube production. The manual pasting operation is initiated by mixing the material of paste with ethanol and followed by the stirring process using a spoon until it turns out to be slightly wet and sticky. Next, the mixture is applied to the electrode wafer using pasting rubber which required consistency, precise and repetitive movement. Therefore, the purpose of this project is to automate the pasting process by introducing the UR10 robot arm robotic system to maintain the desired contact between the rubber pasting and the pasting plate. For that reason, a hybrid force/position-controlled robot system has been developed in a simulation environment. The UR10 robotic system involves a 6-degree of freedom (DOF) articulated robot arm to control the pasting rubber movement, and a force/torque (F/T) sensor system to measure the contact force of the pasting rubber and pasting plate. The UR10 robot arm is simulated using ROS MoveIt and RViz in Ubuntu 18.04 and ROS Melodic before real implementation on a real robot.